i am confused a bit with this equation and i would like someone to explain to me how to solve this
first you need to distribute the 2
then distribute a -1 for the - sign in front of the other. then, combine like terms, isolate your variable and solve.
so 2(x+2) = 2(x) + 2(2) for the first part
the second you are going to do -1(x) and -1(1)
so for the first part you should have 2x+4 right?
so for the 2nd part ou should have -x - 1. put that all together and you have 2x+2-x-1=8
now simplify by combining like terms .. thus x+1 = 8. then you need to move that 1 over to the other side by subtracting it from each side. so x+1-1=8-1 .. now you have x = 8-1
but wjere did u get the -1 from
im sorry.. it should be + 1
o nevermind i got it because of the - sign infront before the x + 1 rifght?
yes it should be x = 8+1 since you have to add 1 to both sides.. my mistake
so here you are looking for x!
first multiply out the 2 with the stuff thats inside the brackets.
and yes.. because of the minus sign. u distribute that as well
now you subtract! 2x-x+4-1=8
here its x+3=8 not subtracy the 3 on both sides. you will get x=8-3 so the x=5
thank you both!!!!
u r weclome :)